HUBUNGAN STATUS ZAT GIZI MIKRO DENGAN STATUS GIZI PADA ANAK REMAJA SLTP - Yuniar Rosmalina; Fitrah Ernawati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2010)
Rational: Good Nutritional status is the basic building block of human capital. To improve the quality of human resources, some attention must be given to the micronutrient and the nutritional status of our human resource. Junior high school students provide the pool of human capital for the future. According to a survey, the micronutrient and nutritional status of these children are still under the satisfactory level. Objectives: To find out the correlation between micronutient status and nutrirional status among junior high school students. Methods: Study design is a cross-sectional. The samples are junior high school at grade one-two and healthy. They were not menstruating and willing to parcipate in this study. Results: This study find out 27.6 % of junior high school were stunted, 6.7% were severely stunted, and 14.7% were underwight. We also find around 37% anemic, 30% were vitamin A deficient, and 41% had zinc deficiency. The average intake of iron, vitamin A and zinc were 40%, 50% and 40% respectively, while the average of energy and protein intake were 60% of RDA. Conclusions: There is no correlation between micronutrient status and nutritional status among the students (height by age/age standart)   Keywords: micronutrient status, nutritional status, zinc status, junior high school